2016
DOI: 10.1038/ijir.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with sexual dysfunction in Brazilian postmenopausal women

Abstract: Sexual function represents an important component of health and life quality. The objective of this study was to assess female sexual function in postmenopausal women and to identify factors associated with sexual dysfunction among this population. From August to December 2013 a cross-sectional study was carried out with 111 postmenopausal, sexually active women aged 45-65 years. A semi-structured questionnaire made up of itemized questions was applied to identify demographic variables, socio-economic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…20,40 Therefore, it would be interesting to assess the effects of marital quality on FSD. Our backward stepwise binary logistic regression indicated that marital quality correlated positively with FSD, which was in accordance with the study by Dombek et al, 41 stating that marital quality had a significant effect on FSD. And, considering that marital quality was poorly understood, 42 health professionals should pay more attention to patients with poor marital quality.…”
Section: Discussionsupporting
confidence: 92%
“…20,40 Therefore, it would be interesting to assess the effects of marital quality on FSD. Our backward stepwise binary logistic regression indicated that marital quality correlated positively with FSD, which was in accordance with the study by Dombek et al, 41 stating that marital quality had a significant effect on FSD. And, considering that marital quality was poorly understood, 42 health professionals should pay more attention to patients with poor marital quality.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Dombek et al16 the rate of sexual dysfunction was reported 70.3% among postmenopausal women. In addition, Jonusiene et al17 reported this rate as 67.9% among postmenopausal women in Lithuania.…”
Section: Methodsmentioning
confidence: 95%
“…According to some studies, ovarian disorders and bladder surgeries were related to sexual dysfunction 16. Based on the results of the study by Nazarpour et al23 the incidence of medical problems in a person or a spouse was suggested as a remarkable factor in the sexual function of menopausal women.…”
Section: Methodsmentioning
confidence: 99%
“…Además existen otros estudios que mencionan a la menopausia asociada a la disfunción sexual (39), pero nuestros resultados no lo evidenciaron; quizás debido a la frecuencia de disfunción sexual en no menopaúsicas que fue 30,9% comparada a 44,26% en menopaúsicas (24).…”
Section: Consideraciones Eticasunclassified